Firm formation in high-tech industries: empirical results for Germany - Eric A. Nerlinger (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
During the last years more and more discussions came up about the contribution of technology-oriented and technology-intensive industries for the economic development and employment. The estimates of the determinants of the regional number of firm formations point out differences between the regions due to different categories: the attractiveness of the county (e.g. infrastructure), the regional endowment with human capital indicated by the location of R&D facilities comprising universities, technical colleges, non-universitary institutes, private R&D, and the regional industry and employment structure. One very surprising finding is that there is no impact of the R&D activities in private firms on the regional number of firm formations in technology intensive industries. However, positive significant effects can be found concerning the regional endowment with e.g. universities depending on the field of specialisation.
Keywords: 330; Unternehmensgründung; Hochtechnologiesektor; Regionale Disparität; Standortfaktor; Deutschland